Interplay of TRIM28 and DNA methylation in controlling human endogenous retroelements - Turelli, Priscilla; Castro-Diaz, Nathaly; Marzetta, Flavia; Kapopoulou, Adamandia; Raclot, Charlène; Duc, Julien; Tieng, Vannary; Quenneville, Simon; Trono, Didier (Genome Research, 2014)
Reverse transcription-derived sequences account for at least half of the human genome. Although these retroelements are formidable motors of evolution, they can occasionally cause disease, and accordingly are inactivated during early embryogenesis through epigenetic mechanisms. In the mouse, at least for endogenous retroviruses, important mediators of this process are the tetrapod-specific KRAB-containing zinc finger proteins (KRAB-ZFPs) and their cofactor TRIM28. The present study demonstrates that KRAB/TRIM28-mediated regulation is responsible for controlling a very broad range of human-specific endogenous retroelements (EREs) in human embryonic stem (ES) cells and that it exerts, as a consequence, a marked effect on the transcriptional dynamics of these cells. It further reveals reciprocal dependence between TRIM28 recruitment at specific families of EREs and DNA methylation. It finally points to the importance of persistent TRIM28-mediated control of ERE transcriptional impact beyond their presumed inactivation by DNA methylation.
10.1101/gr.172833.114